2020
DOI: 10.1038/s41598-020-61490-5
|View full text |Cite
|
Sign up to set email alerts
|

Tead transcription factors differentially regulate cortical development

Abstract: Dagmar iber 3,4 , christian Beisel 5 , erik van nimwegen 2 & Verdon taylor 1* Neural stem cells (NSCs) generate neurons of the cerebral cortex with distinct morphologies and functions. How specific neuron production, differentiation and migration are orchestrated is unclear. Hippo signaling regulates gene expression through Tead transcription factors (TFs). We show that Hippo transcriptional coactivators Yap1/Taz and the Teads have distinct functions during cortical development. Yap1/Taz promote NSC maintenanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
59
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(67 citation statements)
references
References 49 publications
(63 reference statements)
4
59
0
Order By: Relevance
“…Similar to sustained Pax6 expression, but in contrast to Insm1 overexpression, the increased level of BPs observed upon conditional expression of a constitutively-active YAP in the BP lineage showed a decreased proportion of Tbr2+ and an increased proportion of Sox2+ BPs. A similar result of increased proliferation in the SVZ was reported in a very recent, independent study in which Yap mRNA (mYAP) instead of constitutively-active YAP was overexpressed in the NPCs of embryonic mouse neocortex [ 110 ]. However, in contrast to Kostic et al [ 109 ], Mukhtar et al [ 110 ] did not report a decrease in Tbr2+ cells in the SVZ when mYAP was overexpressed.…”
Section: Transcriptional Programs That Regulate Neocortical Neurogsupporting
confidence: 77%
See 1 more Smart Citation
“…Similar to sustained Pax6 expression, but in contrast to Insm1 overexpression, the increased level of BPs observed upon conditional expression of a constitutively-active YAP in the BP lineage showed a decreased proportion of Tbr2+ and an increased proportion of Sox2+ BPs. A similar result of increased proliferation in the SVZ was reported in a very recent, independent study in which Yap mRNA (mYAP) instead of constitutively-active YAP was overexpressed in the NPCs of embryonic mouse neocortex [ 110 ]. However, in contrast to Kostic et al [ 109 ], Mukhtar et al [ 110 ] did not report a decrease in Tbr2+ cells in the SVZ when mYAP was overexpressed.…”
Section: Transcriptional Programs That Regulate Neocortical Neurogsupporting
confidence: 77%
“…A similar result of increased proliferation in the SVZ was reported in a very recent, independent study in which Yap mRNA (mYAP) instead of constitutively-active YAP was overexpressed in the NPCs of embryonic mouse neocortex [ 110 ]. However, in contrast to Kostic et al [ 109 ], Mukhtar et al [ 110 ] did not report a decrease in Tbr2+ cells in the SVZ when mYAP was overexpressed.…”
Section: Transcriptional Programs That Regulate Neocortical Neurogsupporting
confidence: 77%
“…We receptor binding TF activity that has been implicated in mood disorders (Zhou et al 2009;Shi et al 20011;Shyn et al 2011) (Mukhtar et al 2020). Furthermore, KLF11 (Duncan et al 2012;Duncan et al 2015;Harris et al 2015;Kollert et al 2020), SP1 (Brewer et al 2004;Tamayo et al 2009;Pinacho et al 2011;Fuste et al 2013;Saucedo-Uribe et al 2019;Hung et al 2020), andSP4 (Zou et al 2009;Fuste et al 2013;Young et al 2015) have been found to be involved in the genetic regulation of cell-fate and apoptosis as well as in mood and related psychiatric disorders.…”
Section: Degs and Jaspar Tf Motif Identification Of Group-related Difmentioning
confidence: 99%
“…Prenatal HFD exposure can impact DNA methylation of several genes related to dietary fat intake (62,63) as well as the levels and activity of several transcription factors that have been associated with brain development (64), such as transcriptional enhancer factor-1 (TEF-1), yes-associated protein-1 (YAP-1), and the family of peroxisome proliferatoractivated receptors (PPARs), that in turn effect the expression of some of the orexigenic neuropeptides (65)(66)(67)(68). The transcription factors TEF-1 and YAP-1 has been linked to prenatal HFD effects and plays a large role in organ formation and brain development during embryogenesis (69)(70)(71)(72), and activation of these transcription factors have been found to control neuronal proliferation and differentiation (73)(74)(75). Both TEF-1 and YAP-1 were inactivated or decreased during in utero HFD exposure and may promote increased neurogenesis events (65).…”
Section: Dietary Fat On Stimulating Neurochemical Systems In the Hypomentioning
confidence: 99%